Associations between Orosensory Perception of Oleic Acid, the Common Single Nucleotide Polymorphisms (rs1761667 and rs1527483) in the CD36 Gene, and 6-n-Propylthiouracil (PROP) Tasting - Melis, Melania (Nutrients, 2015)
Orosensory perception of dietary fat varies in individuals, thus influencing nutritional status. Several studies associated fat detection and preference with CD36 or 6-n-propylthiouracil (PROP) sensitivity. Other studies have not confirmed the latter association. We analyzed the relationship between orosensory perception of oleic acid, two CD36 variants, and PROP tasting. Thresholds of oleic acid perception were assessed in 64 subjects using a modification of the three-alternative forced-choice procedure. Subjects were classified for PROP taster status and genotyped for TAS2R38 and CD36 (SNPs: rs1761667 and rs1527483). Subjects homozygous for GG of the rs1761667 polymorphism showed higher sensitivity to oleic acid than AA subjects. The capability to detect oleic acid was directly associated with TAS2R38 or PROP responsiveness. PROP non-tasters had a lower papilla density than tasters, and those with genotype GG of the rs1761667 polymorphism had lower oleic acid thresholds than PROP non-tasters with genotype AA. In conclusion, results showed a direct association between orosensory perception of oleic acid and PROP tasting or rs1761667 polymorphism of CD36, which play a significant role in PROP non-tasters, given their low number of taste papillae. Characterization of individual capability to detect fatty acids may have important nutritional implications by explaining variations in human fat preferences.